PENGEMBANGAN VIDEO PEMBELAJARAN INTERAKTIF UNTUK MENINGKATKAN PEMAHAMAN KONSEP SISWA KELAS 1 DALAM MENGUKUR PANJANG BENDA - Layinnatussyifa, Eka; Januar Saputra , Henry; Mandar Sary , Ryky (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop interactive learning video media to improve understanding of the concept of measuring length in grade 1 students of SDN Sumberejo 2. Using the Research and Development (R&D) method with the ADDIE model, involving 29 students as research subjects. Data were collected through observation, interviews, tests, and questionnaires. The video was developed using Canva and CapCut, validated by material experts, media experts, and learning practitioners. The validation results showed a score of 96% from material experts and 97.5% from media experts, which means the video was declared very valid. Implementation was carried out through three meetings, with an average pretest result of 55.17 and increasing to 93.79 in the posttest, with an N-Gain value of 0.8682 which is quite high. This proves that practical videos are used because they can improve student learning outcomes. The effectiveness of the media is proven through the results of the student response questionnaire which reached 94% and the teacher's assessment of 97.5%, both of which are in the "very effective" category. Thus, the interactive learning videos developed are proven to be valid, practical, and effective for use in mathematics learning, especially in the material on measuring length in grade 1 of elementary school.